Improving Students’ Problem-Solving and Numeracy Skills on Circular Motion through STEM Project-Based Learning - Serevina, Vina; Lester, Li-Jen; Yacobi, Muhammad Abrar Asyrafy; Burhanudin, Ahmad Fakhri; Nurbaiti (Jurnal Pendidikan IPA Indonesia, 2026)
This research investigated how STEM-integrated project-based learning (STEM-PjBL) affected students problem solving and numeracy skills in circular motion. The study used a quasi-experimental nonequivalent control group design with 72 tenth-grade students purposively sampled. The experimental group (n = 36) and the control group (n = 36) were assigned two classes. In the experimental group, students were involved in STEM-PjBL that integrated science, technology (T), engineering and mathematics concepts to solve circular motion problems, while control group used conventional instruction. About 30 valid and reliable items on problem solving and numeracy tests were used to collect data. The Shapiro–Wilk normality test, Levene’s homogeneity test as well as ANCOVA, N-gain analysis and Cohen’s d effect size were done at the significance level of 0.05 to analyze the data. The results indicated that the post-test problem-solving skills (N gain = 0.81) and numeracy skills (N gain = 0.78) of the experimental group were better than those of the control group, which attained N-gain scores of 0.48 and 008 respectively. ANCOVA indicated significant group differences (P < 0.05) and of large effect size for problem solving skills(d =1.48) and numeracy skills(d=1.36). The results of these study conclude that STEM-PjBL effectively enhanced students problem solving skills and numeracy in physics learning better than conventional learning.